Campeonato de Futebol "Peladão Indígena": Um olhar sociocultural - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The Amazonian Championship Peladas occurs 40 years ago in the city of Manaus, among the six existing categories - Naked Guy, Main category; Peladinho; Naked Guy Master; Naked Guy Male; Naked Guy Indigenous and Indigenous Male Female Naked Guy - pay attention in this work in two indigenous categories. With the principal of research which sociocultural factors that contribute to the Championship Peladas of Indigenous Peoples goal - Indigenous Naked Guy - remains the main ethnic and cultural-sports event in Manaus. Qualitative research with interdisciplinary support in Physics, Sociology and Anthropology, Education sciences was performed through field research and interviews conducted with leading teams and at least one player from each team who had already participated in at least half of editions. Was also interviewed on two occasions Mr. Arnaldo Santos current event coordinator. As a result it was found that the success and continuity of the event within indigenous categories, is reinforced by presenting a scenario of strong ethno-cultural representation. Also offers participants the opportunity to practical leisure easily assimilated, football.
Keywords: Peladão indígena; Futebol; Socialização; Etnodesporto; CIÊNCIAS HUMANAS